2019
DOI: 10.1192/bjp.2019.30
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder diagnosis in adults: phenotype and genotype findings from a clinically derived cohort

Abstract: BackgroundThe past decade has seen the development of services for adults presenting with symptoms of autism spectrum disorder (ASD) in the UK. Compared with children, little is known about the phenotypic and genetic characteristics of these patients. AimsThis e-cohort study aimed to examine the phenotypic and genetic characteristics of a clinically presenting sample of adults diagnosed with ASD by specialist services. MethodIndividuals diagnosed with ASD as adults were recruited by the National Centre for Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
3
27
1
Order By: Relevance
“…The BDI-II has been utilized extensively over the past two decades, with many studies demonstrating sound psychometric properties and strong diagnostic performance in psychiatric, medical, and general population samples (for a review, see Wang & Gorenstein, 2013). This measure is also one of the most frequently used in studies of autistic adults (Burns et al, 2019; Cederlund et al, 2010; Crane et al, 2013; Gotham et al, 2014; Gotham et al, 2018; Han et al, 2019; Hill et al, 2004; Hillier et al, 2011; Limoges et al, 2005; Russell et al, 2017; Underwood et al, 2019; Unruh et al, 2020). Items on the BDI-II align well with the major depressive disorder criteria in the Diagnostic and Statistical Manual of Mental Disorders–Fifth edition ( DSM-5 ), and a recent study found that the BDI-II has the largest amount of symptom overlap with six other common depression questionnaires (Fried, 2017).…”
mentioning
confidence: 99%
“…The BDI-II has been utilized extensively over the past two decades, with many studies demonstrating sound psychometric properties and strong diagnostic performance in psychiatric, medical, and general population samples (for a review, see Wang & Gorenstein, 2013). This measure is also one of the most frequently used in studies of autistic adults (Burns et al, 2019; Cederlund et al, 2010; Crane et al, 2013; Gotham et al, 2014; Gotham et al, 2018; Han et al, 2019; Hill et al, 2004; Hillier et al, 2011; Limoges et al, 2005; Russell et al, 2017; Underwood et al, 2019; Unruh et al, 2020). Items on the BDI-II align well with the major depressive disorder criteria in the Diagnostic and Statistical Manual of Mental Disorders–Fifth edition ( DSM-5 ), and a recent study found that the BDI-II has the largest amount of symptom overlap with six other common depression questionnaires (Fried, 2017).…”
mentioning
confidence: 99%
“…Volunteers were recruited from the National Centre for Mental Health (NCMH; https://www.ncmh.info/) research cohort, a Welsh Government-funded Biomedical Research Centre, operated by Cardiff, Swansea and Bangor Universities, in partnership with National Health Service (NHS) Health Boards across Wales (31). NCMH collects biological samples, clinical data, and socioeconomic information from people across the lifespan with a history of neurodevelopmental, psychiatric, and neurodegenerative disorders and also from healthy control participants.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, authors demonstrated an increased reported rate of migraine: 42.7% of individuals with ASD reported a lifetime history of migraine compared to 20.5% of controls ( p = 0.012). There was also a higher rate of epilepsy and seizures compared to controls and an association between migraine and epilepsy was confirmed ( p = 0.028) [ 21 ].…”
Section: Co-occurring Asd-migraine Epidemiologymentioning
confidence: 99%